MANAJEMEN KEHADIRAN BERBASIS TEKNOLOGI: EFEKTIVITAS ABSENSI FINGERPRINT DALAM MENINGKATKAN DISIPLIN GURU DAN KARYAWAN DI LEMBAGA PENDIDIKAN - Aqsyal Ilham Syachbana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Technological developments in the Industry 4.0 era have drivendigital transformation in various sectors, including education. One of theinnovations is the application of a fingerprint-based attendance system toimprove the discipline of teachers and employees in educational institutions. This study aims to analyze the effectiveness of using fingerprints inimproving discipline, identify obstacles in its implementation,and evaluate the perceptions of teachers and employees towards this system. The research methodused library research with a qualitative approachto collect and analyze data from various literature sources. The results show that the fingerprint attendance systemis effective in improving discipline due to its accuracy,transparency, and resistance to manipulation. Its advantages include the prevention offraud such as proxy attendance, administrative efficiency, and increasedwork productivity. However, there are several obstacles to its implementation,such as user adaptation to technology and infrastructure limitations.The perceptions of teachers and employees are generally positive, with this system being considered anobjective and fair monitoring tool. This study provides recommendationsfor educational institutions to optimize the use of fingerprint technologythrough user training and infrastructure improvements. A significant impactcan be seen in the improvement of a culture of discipline, accountability, and efficiencyin human resource management.